Al-Ajru dalam Perspektif Ra’yu Zamakhsyariy (Studi Tematis Kitab Tafsir al-Kasyaf) - Anggi Wahyu Ari; Rudi Kurniawan (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
The discussion of reward is often the object of aqidah study for theologians and scholars of kalam. Therefore, in this study the author makes the interpretation of Al-Kasyaf by al-Zamakhsyari (467-538 H) as an object of study that leads to a more complete and deeper study of the science of kalam. In the interpretation of Al-Kasyaf, al-Zamakhsyari uses logic more and this is what is used as a material for criticism by some scholars as material for defending the muktazilah understanding that he believes in. Sometimes he berates the leading priests astray, especially if they have an opinion that contradicts him. This paper tries to describe Zamakhsyari's interpretation of the reward in the perspective of the Koran from Tafsir Al-Kasyaf from the word al-ajr. This paper uses the maudhu'i method through an approach to understanding the characters in his work. The results of the study show that the term ajr that appears in the Koran is always related to human actions in good things or about goodness. The existence of ajr from Allah Swt cannot be separated from the role of human good deeds. Various virtues that are present with Ajr, besides the goodness mentioned earlier, there are other virtues, such as piety and patience, striving in the way of Allah, and always remembering Allah. Although ajr is closely related to the good deeds that have been done, the source of ajr itself is essentially from Allah Swt.